Space Vector Modulation Strategy for Three Level Boost Inverter with Reduction Total Harmonic Distortion - Do, Đức Trí; Tran, Lê Huy; Van, Tấn Lương; Le, Hoàng Minh (Journal of Technical Education Science, 2023)
Recently, several pulse width modulation techniques have been studied by three-level impedance-source inverters. The space vector modulation (SVM) technology with upper and lower shoot-through (UST/LST) insertion is one of the studies that offers high voltage gain and better output voltage quality. This study presents inductor current ripple of the TL-qSBI is lessened by the SVPWM strategy. The shoot-through duty cycle is kept constant in the proposed SVPWM strategy to keep the modulation index as high as possible. Then the duty cycles of the two power switches of the impedance source network are the only control parameters for the TL-qSBI. The voltage gain of the qSBT2I can be increased to a value greater than that of the traditional three-level impedance source inverters by adjusting the duty cycles of the two power switches of the impedance source network. The operational principles and the steady-state analysis are presented. Experimental results are validated by the theoretical analysis.